Hubungan Antara Penyesuaian Diri dengan Manajemen Diri pada Anggota Pimpinan Cabang Ikatan Pelajar Muhammadiyah Srandakan - Astuti Mei Wulandari; Mustaqim Setyo Ariyanto (EduInovasi: Journal of Basic Educational Studies, 2025)
Being organized is important for students because it can provide benefits for self-development, both academically and non-academically. The Muhammadiyah Student Association (IPM) is an autonomous Muhammadiyah organization that operates among students and teenagers. The purpose of this study was to determine the relationship between self-adjustment and self-management in members of the Muhammadiyah Student Association Srandakan Branch Leadership. This study focuses on the analysis of the relationship between self-adjustment and self-management in members of the IPM Srandakan Branch Leadership. The respondents in this study were members of the Muhammadiyah Student Association Srandakan Branch Leadership. The data collection method used in this study was a scale. This research method uses a quantitative method with a correlational approach. Research data can be obtained by a questionnaire that measures self-management skills with self-adjustment of PC IPM Srandakan members. The results of the hypothesis test obtained in this study are that there is a relationship between the variables of self-adjustment and self-management as indicated by a sig (2-tailed) value of 0.00 or P <0.01 with a coefficient value of 0.843 so that it can be interpreted that there is a close relationship between self-adjustment and self-management. It can be concluded that the variables of self-adjustment with self-management have a positive or unidirectional relationship. This means that the higher the level of self-management of members, the higher the level of self-adjustment and vice versa.